STRATEGI PENINGKATAN PRODUKSI GULA SEMUT DI DESA MANGKAWANI KABUPATEN ENREKANG - M. Tang; Al Gazali; Ahmad Jumarding (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2021)
Nira Aren in Mangkawani Village is quite abundant but the community is able to produce printed brown sugar. In addition to the production of printed brown sugar, the community also produces palm sugar in a simple way and drying ant sugar by using sunlight. The service activity aims to help partners as a target group to increase the production of quality ant sugar and also assist the use of ant palm sugar dryers to maintain product quality and be more durable and help how to promote ant sugar products in online media. The service team partnered with KWT Mawar Jingga Mangkawani. The activities carried out are 1) the application of the ant palm sugar drying machine to partners. 2) Guidance and training on product packaging and designing packaging labels. The methods used are: a) procurement of ant palm sugar drying machine b) socialization, training and mentoring. From the results of the service activities, they have produced ant palm sugar products with attractive packaging and support the ant palm sugar production process with the presence of a drying machine.